Analysis of the Impact of Tourist Visits on the Culture of the Community Around the Batu Kuda Tourist Area, Bandung Regency - Ramdani, Dadan (International Journal of Humanities, Education, and Social Sciences, 2025)
This research investigates the socio-cultural impacts of tourism in the Batu Kuda tourist area, Bandung Regency, focusing on how interactions between tourists and local residents influence cultural values. Batu Kuda, known for its natural beauty and tranquil atmosphere, has experienced a steady rise in tourist visits, leading to both economic benefits and cultural transformations within the local community. The study aims to analyze the positive and negative cultural impacts of tourism activities and to explore community responses to these changes. Additionally, it seeks to provide recommendations for tourism managers and village authorities to help maintain a balance between tourism development and cultural preservation. Employing a descriptive qualitative approach, data were collected through in-depth interviews with key informants, including tourism managers, MSME operators, village officials, and tourists, conducted directly at the site. Thematic analysis revealed that increased tourism has positively contributed to community income and entrepreneurial growth, particularly in the MSME sector. However, it has also led to shifts in social values, including decreased cultural awareness, adoption of external lifestyle trends, and rising environmental concerns. While some community members demonstrate awareness and adaptability, others remain unprepared for these shifts. The study concludes that promoting sustainable tourism requires a management strategy rooted in local wisdom, alongside educational initiatives for tourists, to safeguard cultural identity and ensure long-term environmental and cultural sustainability.